The science of screenwriting the neuroscience behind storytelling strategies - Gulino, Paul Joseph; Shears, Connie (New York Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2018)
"In a world awash in screenwriting books, The Science of Screenwriting provides an alternative approach that will help the aspiring screenwriter navigate this mass of often contradictory advice: exploring the science behind storytelling strategies. Paul Gulino, author of the best-selling Screenwriting: The Sequence Approach, and Connie Shears, a noted cognitive psychologist, build, chapter-by-chapter, an understanding of the human perceptual/cognitive processes, from the functions of our eyes and ears bringing real world information into our brains, to the intricate networks within our brains connecting our decisions and emotions. They draw on a variety of examples from film and television -- The Social Network, Silver Linings Playbook and Breaking Bad -- to show how the human perceptual process is reflected in the storytelling strategies of these filmmakers. They conclude with a detailed analysis of one of the most successful and influential films of all time, Star Wars, to discover just how it had the effect that it had"--Provided by publisher.
Introduction; or, should I save the cat and send the hero on his journey? -- The science of information flow, or, I say schema, you say schemata: top-down vs. bottom-up -- The science of connecting to the main character, or, why do i worry that a meth dealer might get caught? -- Science of contrast, or, why the big huge spaceship followed the little tiny space ship in the opening of Star Wars -- The science of exposition, or, what's wrong with an information dump? -- Science of cause and effect, or, did the Packers really lose because I didn't wear my cheesehead hat? -- The science of shared attention, or if I write a screenplay in which a tree falls in the forest, and the reader falls asleep halfway through, have i written a screenplay? -- The science of conflict, or, what's wrong with watching two hours of people just getting along and helping each other? -- Science of imagination: temporal lobes, how to think creatively, stages of mind, or, your dope-fueled imaginings -- The structure question, or, how many acts does it take to sell a script? -- Star Wars, or, how George did it.
Includes bibliographical references (pages 159-162) and index.
Keywords: Motion picture authorship; Motion picture authorship -- Psychological aspects; Neurosciences -- Popular works